The effects of tumor resection and adjuvant therapy on the peripheral blood immune cell profile in patients with colon carcinoma - Krijgsman, Daniëlle (Cancer Immunol Immunother, 2020)
OBJECTIVE: The subset distribution and immunophenotype of circulating immune cells (“peripheral blood immune cell profile”) may reflect tumor development and response to cancer treatment. In order to use the peripheral blood immune cell profile as biomarker to monitor patients over time, it is crucial to know how immune cell subsets respond to therapeutic interventions. In this study, we investigated the effects of tumor resection and adjuvant therapy on the peripheral blood immune cell profile in patients with colon carcinoma (CC). METHODS: The subset distribution and immunophenotype of T cells (CD3(+)CD56(−)), CD56(dim) NK cells (CD3(−)CD56(dim)), CD56(bright) NK cells (CD3(−)CD56(bright)) and NKT-like cells (CD3(+)CD56(+)) were studied in preoperative and postoperative peripheral blood mononuclear cell (PBMC) samples of 24 patients with CC by multiparameter flow cytometry. Changes in immunophenotype of circulating immune cells after tumor resection were studied in patients treated with and without (capecitabine-based) adjuvant therapy. RESULTS: The NKT-like cell (% of total PBMCs) and CD8(+) T cell (% of total T cells) populations expanded in the peripheral blood of non-adjuvant-treated CC patients after surgery. NK- and NKT-like cells showed upregulation of activating receptors and downregulation of inhibitory receptors in non-adjuvant-treated CC patients after surgery. These changes were not observed in the peripheral blood of adjuvant-treated CC patients. CONCLUSIONS: Our results suggest tumor-induced suppression of NK- and NKT-like cells in CC patients, an effect that could not be detected after tumor resection. In contrast, adjuvant therapy maintained tumor-induced immunosuppression of NK- and NKT-like cells in CC patients.